2022
DOI: 10.3389/fpls.2021.751429
|View full text |Cite
|
Sign up to set email alerts
|

Agro-Morphological Characterization of Lentil Germplasm of Indian National Genebank and Development of a Core Set for Efficient Utilization in Lentil Improvement Programs

Abstract: Lentil (Lens culinaris Medik.) is one of the major cool-season pulse crops worldwide. Its increasing demand as a staple pulse has led to the unlocking of diverse germplasm collections conserved in the genebanks to develop its superior varieties. The Indian National Genebank, housed at the Indian Council of Agricultural Research (ICAR)-National Bureau of Plant Genetic Resources, New Delhi, India, currently has 2,324 accessions comprising 1,796 indigenous and 528 exotic collections. This study was conducted to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 62 publications
(80 reference statements)
6
16
0
Order By: Relevance
“…Thus, to study various other seed parameters like area, length, width, compactness, volume, and perimeter, this study for the first time used the state-of-the-art VideometerLab instrument and very precise data were generated using 20 replicates. As recorded for this study, previous studies also revealed large variations in seed weight and diameters in lentils ( Tullu et al, 2001 ; Tripathi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 85%
“…Thus, to study various other seed parameters like area, length, width, compactness, volume, and perimeter, this study for the first time used the state-of-the-art VideometerLab instrument and very precise data were generated using 20 replicates. As recorded for this study, previous studies also revealed large variations in seed weight and diameters in lentils ( Tullu et al, 2001 ; Tripathi et al, 2022 ).…”
Section: Discussionsupporting
confidence: 85%
“…Promising germplasm lines have been identified for various agronomic traits, such as seedling vigor, earliness, number of pods/peduncle, number of pods/plant, and seed weight ( Singh., 1995 ). In another large-scale characterization conducted at the ICAR–NBPGR, accessions were characterized on 26 agro-morphological traits, and a core set of 170 accessions was developed ( Tripathi et al, 2021a ). Kumar et al (2013) have also highlighted important lines for traits such as winter hardiness, short duration type, mechanical harvesting, and higher seed weight.…”
Section: Utilization Of Grain Legume Germplasm For Crop Improvementmentioning
confidence: 99%
“…Generally, microsperma types are more common in southeast Asia, while macrosperma types in western Asia and Europe ( Barulina, 1930 ). Previous genetic studies revealed large variations for seed weight and seed diameter in lentils ( Tullu et al., 2001 ; Dutta et al., 2022 ; Tripathi et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seed weight is known to be governed by several genes and thus identification of linked markers with the seed weight QTLs will help in the better selection for this trait. This will also help in speeding up of new variety development having desired seed parameters ( Tripathi et al., 2022 ). Also, for the implementation of molecular breeding approach for seed size trait, there is a need for the development of an experimental population involving contrasting parents, so that the linkage can be established between marker and the trait.…”
Section: Introductionmentioning
confidence: 99%